Role of Creativity in the Effectiveness of Cognitive Reappraisal - Wu, Xiaofei; Guo, Tingting; Tang, Tengteng; Shi, Baoguo; Luo, Jing (Frontiers in Psychology, 2017)
As a well-recognized and widely adopted emotional regulation strategy, cognitive reappraisal has generally been proven to be efficient. However, the cognitive mechanism underlying regulatory efficiency, particularly the role of creativity, in cognitive reappraisal is unclear. Although previous studies have evaluated the relationship between creativity and reappraisal from the perspectives of generation (i.e., generating cognitive reappraisals and generating creative ideas involve similar cognitive neural networks) and individual differences (i.e., the ability to generate different cognitive reappraisals can be predicted by scores on creativity-related tests), how cognitive reappraisal’s efficiency can be related to creativity is still unknown. In this research, we assessed the relationship between cognitive reappraisal’s creativity and its effectiveness in regulating negative emotion. In Study 1, participants were asked to generate reappraisals of negative stimuli and then evaluate the creativity and regulatory effectiveness of these reappraisals. The results indicated positive correlation between creativity rating and regulatory effectiveness, but we found that it was difficult for the participants to generate highly creative reappraisals on their own. Therefore, in Study 2, we showed participants well-prepared reappraisal materials that varied in their creativity and asked them to evaluate their regulatory effectiveness and creativity. The results suggested that creativity and appropriateness were significant predictors of the regulating effects of the reappraisal and that creativity was the most dominant predictor. In summary, both experiments found a positive correlation between reappraisal’s creativity and effectiveness, thus implying that creativity plays an important role in reappraisal.